2012
DOI: 10.1038/ncomms2128
|View full text |Cite
|
Sign up to set email alerts
|

A combinatorial extracellular matrix platform identifies cell-extracellular matrix interactions that correlate with metastasis

Abstract: Extracellular matrix interactions play essential roles in normal physiology and many pathological processes. While the importance of ECM interactions in metastasis is well documented, systematic approaches to identify their roles in distinct stages of tumorigenesis have not been described. Here we report a novel screening platform capable of measuring phenotypic responses to combinations of ECM molecules. Using a genetic mouse model of lung adenocarcinoma, we measure the ECM-dependent adhesion of tumor-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
168
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(173 citation statements)
references
References 48 publications
2
168
1
2
Order By: Relevance
“…These results demonstrate that epithelial confinement alone can induce morphogenetic-like processes including spontaneous collective pulsations and transition from two-dimensional (2D) to threedimensional (3D) morphology. These findings are likely to have direct practical implications since the trend towards miniaturization of cell culture platforms directly results in confined small-size cell populations 7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate that epithelial confinement alone can induce morphogenetic-like processes including spontaneous collective pulsations and transition from two-dimensional (2D) to threedimensional (3D) morphology. These findings are likely to have direct practical implications since the trend towards miniaturization of cell culture platforms directly results in confined small-size cell populations 7 .…”
mentioning
confidence: 99%
“…However, the collective behaviour of well-defined cell groups is also involved in other situations such as the response of cancer cell assemblies to compression 4,5 or the adaptation and evolution of tumours that have been proposed to be described by very generic processes 6 . On a different note, high-density newgeneration cell chips operate at these mesoscales to analyse populations of a few hundred cells 7 , and tissue engineering strategies now aim at a very accurate spatial relative and absolute positioning of groups of cells of different types 8 .…”
mentioning
confidence: 99%
“…Indeed, the frequency of lymph node metastasis is completely abolished upon silencing of Gal-8 in a mouse model of prostate cancer (45). Similarly, binding of lung cancer cells to Gal-8 in combination with fibronectin is strongly associated with metastatic progression of lung adenocarcinoma (51). Still, a number of studies reported on decreased expression of Gal-8 in association with favorable early tumor progression (52,53).…”
Section: B Gal-8 and Cancermentioning
confidence: 99%
“…Galectin-glycan lattices create homotypic or glycoprotein complexes that are involved in cellular signaling related to a variety of cell functions, including cell adhesion, migration, invasion, angiogenesis, immune functions, apoptosis, and endocytosis (Garner and Baum, 2008;Nangia-Makker et al, 2008;Chiu et al, 2010;Çay, 2012). During the ECM remodeling, new Gal-3-glycan lattices occur and mediate new interactions (Lagana et al, 2006;Reticker-Flynn et al, 2012;Priglinger et al, 2013). Galectin-glycoprotein lattices control the organization of plasma membrane domains like lipid rafts and the direction of targeted delivery of glycoproteins to the cell surface.…”
Section: Elongation Of the Oligosaccharide Chains Polylacnacs And Gmentioning
confidence: 99%